A novel small‐molecule activator of procaspase‐3 induces apoptosis in cancer cells and reduces tumor growth in human breast, liver and gallbladder cancer xenografts. Issue 8 (3rd July 2014) - Wang, Fangyang; Wang, Lihui; Zhao, Yanfang; Li, Yi; Ping, Guanfang; Xiao, Shu; Chen, Kang; Zhu, Wufu; Gong, Ping; Yang, Jingyu; Wu, Chunfu
Abstract : Purpose: Procaspase‐3, a proenzyme of apoptotic executioner caspase‐3, is overexpressed in numerous tumors. We aimed to characterize a novel procaspase‐3 activator, WF‐210, which may have potential as an anticancer drug. Experimental design: The procaspase‐3 activating ability, antitumor efficacy, mechanisms of action, and toxicity profiles of WF‐210 were investigated in vitro and in vivo, using normal cells, cancer cells, and mouse xenograft models. The role of procaspase‐3 in WF‐210‐induced apoptosis was explored by manipulating procaspase‐3 expression in cultured cells. Results: WF‐210 activated procaspase‐3 with an EC50 of 0.95 μM, less than half that of its mother compound PAC‐1 (2.08 μM). The mechanism involved the chelation of inhibitory zinc ions, subsequently resulting in an auto‐activation of procaspase‐3. WF‐210 was more cytotoxic than PAC‐1 to human cancer cells, but less cytotoxic to normal cells. Cancer cells with high procaspase‐3 expression, like HL‐60 and U‐937, were particularly sensitive. WF‐210‐induced the apoptosis of HL‐60 and U‐937 cells by activating procaspases and promoting proteasome‐dependent degradation of XIAP and Survivin. The level of WF‐210‐induced apoptosis in cultured cells was related to the level of procaspase‐3 expression. Finally, WF‐210 was superior to PAC‐1 in retarding the in vivo growth of breast, liver and gallbladder xenograft tumors which overexpress procaspase‐3, and induced no substantial weight loss or neurotoxicity. WF‐210 and PAC‐1 had no effect on the growth of MCF‐7 xenograft tumors, which do not express procaspase‐3. Conclusion: We identified WF‐210 as a potent small‐molecule activator of procaspase‐3. The favorable antitumor activity and acceptable toxicity profile of WF‐210 provide a strong rationale for its clinical evaluation in the treatment of tumors with high procaspase‐3 expression. Highlights: We discovered a novel procaspase‐3 activator WF‐210. We demonstrated that WF‐210 has higher selection index. We found that WF‐210 could induce tumor cell apoptosis through activate procaspase‐3. WF‐210 or PAC‐1 induced apoptosis by promoting proteasome‐dependent degradation of IAPs. WF‐210 showed greater therapeutic effect in vivo compared with PAC‐1.